1986
DOI: 10.1128/aem.51.4.690-693.1986
|View full text |Cite
|
Sign up to set email alerts
|

Fungitoxic effects of nonprotein imino acids on growth of saprophytic fungi isolated from the leaf surface of Calliandra haematocephala

Abstract: Four saprophytic and pathogenic fungi were isolated from the leaf surface of Calliandra haematocephala, a tropical legume known to contain large amounts of rare nonprotein imino acids in its leaves and seeds. The fungi Aspergilus niger, Aspergillus sp., Curvularia sp., and Penicilliutn sp. were cultured in the laboratory and tested for susceptibility to leaf extracts of the host plant and to proline, pipecolic acid, cis-5-hydroxypipecolic acid, and 2,4-trans-4,5-cis-4,5-dihydroxypipecolic acid. Fungal spore ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The current data showed that K, Zn, and Fe are present in greater quantities in the rachis of both wheat cultivars. The function of metal ions in plant disease resistance varies; it is known that the fungal-spore germination and plant infection is stimulated by compounds exuded from the plant (Brenner and Romeo, 1986 ; Steinkellner et al, 2005 ). In this study, the Ca content was substantially higher in SU3 than in MM after infection, which may indicate the relevance of this element to FHB resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The current data showed that K, Zn, and Fe are present in greater quantities in the rachis of both wheat cultivars. The function of metal ions in plant disease resistance varies; it is known that the fungal-spore germination and plant infection is stimulated by compounds exuded from the plant (Brenner and Romeo, 1986 ; Steinkellner et al, 2005 ). In this study, the Ca content was substantially higher in SU3 than in MM after infection, which may indicate the relevance of this element to FHB resistance.…”
Section: Discussionmentioning
confidence: 99%
“…10 The decoction of C. californica (Benth), locally known as "Tabardillo", is used in Baja California to treat kidney ache, cystitis, urethritis and gall stones, also the plant extract has antimicrobial activity and can inhibit prostaglandin synthetase activity. 12 Generally, the biological studies on genus Calliandra stated that it has antimicrobial, 14,15 insecticidal, 16,17 molluscicidal, 18 antiulcerogenic, anticholinergic 10 and anticonvulsant activities. 11 As for Calliandra haematocephala, the decoction of the flower is said to be blood purifier and tonic.…”
Section: Introductionmentioning
confidence: 99%
“…46,119,120 Marlier et al 57 isolated 4,5-dihydroxy-L-pipecolic acid from Calliandra haematocephala, and C-4 oxygenated derivatives of pipecolic acid, including (2S, 4R)-4-hydroxypipecolic acid, were reported from the leaves of Calliandra pittieri and Strophanthus scandeus. 45 Marlier et al 58 isolated 2S-carboxy-4R,5S-dihydroxypiperidine and 2S-carboxy-4S, 5S-dihydroxypiperidine derived from pipecolic acid from the leaves of Derris elliptica; 2,4-trans-4,5-trans-4,5dihydroxypipecolic acid, cis-5-hydroxypipecolic acid (antifungal), 118 and trans-5-hydroxypipecolic acid (inhibitor of larvae growth) 117 were detected in the leaves of Calliandra angustifolia. 59 Uracilderived secondary metabolites of plants, including lathyrine metabolic modification, lead to the occurrence of cis-5-hydroxy-L-pipecolic acid.…”
Section: Pipecolic Acid Derivatives Of Plant Originmentioning
confidence: 99%